Family Visitation as a Therapeutic Space: A Phenomenological Study on Inmate Counseling - Ilahi, Ach. Firman; Arifin, Samsul; Gopar, Abdul; Mirza, Ahmad; Atiq, Choirul; Putra, Dimas Anggara (Universitas Islam Negeri Sunan Kudus, 2026)
Family visitation in correctional institutions has consistently been associated with improved psychological well-being and rehabilitation outcomes among incarcerated individuals; however, existing research remains largely quantitative and outcome-focused, offering limited theoretical insight into the relational and therapeutic mechanisms underlying these effects from a counseling perspective. Addressing this gap, the present phenomenological study explores the lived experiences of incarcerated individuals during family visits and examines the relational dynamics that emerge through the lens of systemic family counseling. Using Interpretative Phenomenological Analysis (IPA), in-depth semi-structured interviews were conducted with nine male incarcerated individuals and five family members in an Indonesian correctional facility. The analysis revealed that family visitation constitutes a multidimensional and dialectical experience, simultaneously providing existential validation, emotional reassurance, and identity reinforcement, while also eliciting ambivalent emotions such as guilt, vulnerability, and anticipatory loss. Visitation encounters functioned as systemic microcosms in which core therapeutic processes—emotional co-regulation, narrative reconstruction of self and family roles, and protective relational communication aimed at managing conflict and preserving hope—unfolded organically. These findings support a conceptual reframing of family visitation as a naturally occurring systemic therapeutic intervention, rather than a peripheral institutional routine. The study carries important implications for counseling practice in correctional settings, highlighting the need to strategically integrate family visitation into structured pre-visit preparation and post-visit counseling processes to enhance psychological recovery and support reintegration trajectories.